Co-Targeting of BTK and TrxR as a Therapeutic Approach to the Treatment of Lymphoma - Sicong Wang; Erin Clapper; Kathryn F. Tonissen; Giovanna Di Trapani (MDPI AG, 2023)
Diffuse large B-cell lymphoma (DLBCL) is a haematological malignancy representing the most diagnosed non-Hodgkin's lymphoma (NHL) subtype. Despite the approved chemotherapies available in clinics, some patients still suffer from side effects and relapsed disease. Recently, studies have reported the role of the Trx system and the BCR signalling pathway in cancer development and drug resistance. In this regard, we assessed a potential link between the two systems and evaluated the effects of [Au(d2pype)2]Cl (TrxR inhibitor) and ibrutinib (BTK inhibitor) alone and in combination on the cell growth of two DLBCL lymphoma cell lines, SUDHL2 and SUDHL4. In this study, we show higher expression levels of the Trx system and BCR signalling pathway in the DLBCL patient samples compared to the healthy samples. The knockdown of TrxR using siRNA reduced BTK mRNA and protein expression. A combination treatment with [Au(d2pype)2]Cl and ibrutinib had a synergistic effect on the inhibition of lymphoma cell proliferation, the activation of apoptosis, and, depending on lymphoma cell subtype, ferroptosis. Decreased BTK expression and the cytoplasmic accumulation of p65 were observed after the combination treatment in the DLBCL cells, indicating the inhibition of the NF-κB pathway. Thus, the co-targeting of BTK and TrxR may be an effective therapeutic strategy to consider for DLBCL treatment.